2009
DOI: 10.1039/b822578h
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid tissue analysis through Raman spectroscopy

Abstract: The diagnosis of thyroid pathologies is usually made by cytologic analysis of the fine needle aspiration (FNA) material. However, this procedure has a low sensitivity at times, presenting a variation of 2-37%. The application of optical spectroscopy in the characterization of alterations could result in the development of a minimally invasive and non-destructive method for the diagnosis of thyroid diseases. Thus, the objective of this work was to study the biochemical alterations of tissues and hormones (T3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 8 publications
5
31
0
Order By: Relevance
“…Raman spectroscopy has been applied to examine normal and cancerous thyroid tissues ex vivo and thyroid cell lines in vitro [10,11,13,14 [11]. The Raman peaks employed in this in situ cellular level thyroid study (Table 1) are overall in agreement with the peaks observed in earlier ex vivo and in vitro studies.…”
Section: Raman Spectroscopy Of the Thyroidsupporting
confidence: 66%
See 2 more Smart Citations
“…Raman spectroscopy has been applied to examine normal and cancerous thyroid tissues ex vivo and thyroid cell lines in vitro [10,11,13,14 [11]. The Raman peaks employed in this in situ cellular level thyroid study (Table 1) are overall in agreement with the peaks observed in earlier ex vivo and in vitro studies.…”
Section: Raman Spectroscopy Of the Thyroidsupporting
confidence: 66%
“…The Raman peaks employed in this in situ cellular level thyroid study (Table 1) are overall in agreement with the peaks observed in earlier ex vivo and in vitro studies. It is important to note that in general, thyroid tissue is very complex as there are a large number of functional groups vibrating at the same time [10,11]. Therefore, there is significant value in performing Raman spectroscopic analysis on specific cellular level structures within the thyroid.…”
Section: Raman Spectroscopy Of the Thyroidmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, an optic biopsy technique for the study of oncological lesions was used, FT-Raman spectroscopy, a method which supplies information on the molecular structure of the sample under examination [3][4][5] . This technique has specific characteristics, appropriate for the study of the skin, both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses primarily on the use of fluorescence spectroscopy (4-6), time-resolved fluorescence (7,8), near-infrared spectroscopy (9-11), Raman spectroscopy (12,13), infrared spectroscopy (14)(15)(16)(17), elastic scattering spectroscopy (18,19), second-harmonic generation (SHG) microscopy (20,21), and optical coherence tomography (22)(23)(24) to evaluate thyroid and parathyroid tissues.…”
Section: Introductionmentioning
confidence: 99%